Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's go through the step-by-step solution to solve the equation [tex]\(8x^2 - 48x = -104\)[/tex].
1. Normalize the Quadratic Equation:
We start by rewriting the given quadratic equation so that the coefficient of [tex]\(x^2\)[/tex] is 1. To do this, we will divide every term in the equation by 8:
[tex]\[ \frac{8x^2 - 48x}{8} = \frac{-104}{8} \][/tex]
Simplifying this, we get:
[tex]\[ x^2 - 6x = -13 \][/tex]
2. Completing the Square:
Next, we need to complete the square on the left-hand side of the equation. To do that, we take the coefficient of [tex]\(x\)[/tex], divide it by 2, and then square it. The coefficient of [tex]\(x\)[/tex] here is -6:
[tex]\[ \left(\frac{-6}{2}\right)^2 = (-3)^2 = 9 \][/tex]
We add and subtract this value on the left-hand side:
[tex]\[ x^2 - 6x + 9 - 9 = -13 \][/tex]
[tex]\[ x^2 - 6x + 9 = -13 + 9 \][/tex]
3. Simplify the Equation:
Now simplify both sides:
[tex]\[ x^2 - 6x + 9 = -4 \][/tex]
4. Factor the Completed Square:
The left-hand side is now a perfect square trinomial, which can be factored as:
[tex]\[ (x - 3)^2 = -4 \][/tex]
5. Solve for x:
To solve for [tex]\(x\)[/tex], we need to take the square root of both sides. Recall that taking the square root of a negative number will introduce the imaginary unit [tex]\(i\)[/tex]:
[tex]\[ x - 3 = \pm \sqrt{-4} \][/tex]
[tex]\[ x - 3 = \pm 2i \][/tex]
6. Isolate x:
Finally, we solve for [tex]\(x\)[/tex] by adding 3 to both sides of the equation:
[tex]\[ x = 3 \pm 2i \][/tex]
Therefore, the solutions to the equation [tex]\(8x^2 - 48x = -104\)[/tex] are:
[tex]\[ x = 3 + 2i \quad \text{and} \quad x = 3 - 2i \][/tex]
1. Normalize the Quadratic Equation:
We start by rewriting the given quadratic equation so that the coefficient of [tex]\(x^2\)[/tex] is 1. To do this, we will divide every term in the equation by 8:
[tex]\[ \frac{8x^2 - 48x}{8} = \frac{-104}{8} \][/tex]
Simplifying this, we get:
[tex]\[ x^2 - 6x = -13 \][/tex]
2. Completing the Square:
Next, we need to complete the square on the left-hand side of the equation. To do that, we take the coefficient of [tex]\(x\)[/tex], divide it by 2, and then square it. The coefficient of [tex]\(x\)[/tex] here is -6:
[tex]\[ \left(\frac{-6}{2}\right)^2 = (-3)^2 = 9 \][/tex]
We add and subtract this value on the left-hand side:
[tex]\[ x^2 - 6x + 9 - 9 = -13 \][/tex]
[tex]\[ x^2 - 6x + 9 = -13 + 9 \][/tex]
3. Simplify the Equation:
Now simplify both sides:
[tex]\[ x^2 - 6x + 9 = -4 \][/tex]
4. Factor the Completed Square:
The left-hand side is now a perfect square trinomial, which can be factored as:
[tex]\[ (x - 3)^2 = -4 \][/tex]
5. Solve for x:
To solve for [tex]\(x\)[/tex], we need to take the square root of both sides. Recall that taking the square root of a negative number will introduce the imaginary unit [tex]\(i\)[/tex]:
[tex]\[ x - 3 = \pm \sqrt{-4} \][/tex]
[tex]\[ x - 3 = \pm 2i \][/tex]
6. Isolate x:
Finally, we solve for [tex]\(x\)[/tex] by adding 3 to both sides of the equation:
[tex]\[ x = 3 \pm 2i \][/tex]
Therefore, the solutions to the equation [tex]\(8x^2 - 48x = -104\)[/tex] are:
[tex]\[ x = 3 + 2i \quad \text{and} \quad x = 3 - 2i \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.